How Does AI Detect Glaucoma from Retinal Images? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2018)
Glaucoma, a leading cause of irreversible blindness worldwide, is an optic nerve disease that results in progressive vision loss [1]. Early detection and dia...
Keywords: AI in Ophthalmology; Detect; Glaucoma; Retinal; Artificial Intelligence; Deep Learning